Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s11434-011-4755-x
|View full text |Cite
|
Sign up to set email alerts
|

Globalization and long-run co-movements in the stock market for the G7: An application of VECM under structural breaks

Abstract: This paper analyzes the process of long-run co-movements and stock market globalization on the basis of cointegration tests and vector error correction (VEC) models. The cointegration tests used here allow for structural breaks to be explicitly modeled and breakpoints to be computed on a relative-time basis. The data used in our empirical analysis were drawn from Datastream and comprise the natural logarithms of relative stock market indexes since 1973 for the G7 countries. The main results point to the conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…They showed that integrating these different stock markets induced rising co-movements in prices, returns, correlation, and volatility. Menezes and Dionísio ( 2011 ) used a VECM model under structural breaks to investigate the long-run co-movements and globalization in G7 stock markets and found a significant long-run causal relationship across the process of G7 market integration, driven in general by the US stock market. Tsai ( 2014 ) investigated the spillover effect in the main five stock markets (US, UK, Germany, Japan, and France) and found a net spillover effect in the US stock market during the subprime mortgage crisis and Lehman Brothers bankruptcy from 2007 to 2008.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They showed that integrating these different stock markets induced rising co-movements in prices, returns, correlation, and volatility. Menezes and Dionísio ( 2011 ) used a VECM model under structural breaks to investigate the long-run co-movements and globalization in G7 stock markets and found a significant long-run causal relationship across the process of G7 market integration, driven in general by the US stock market. Tsai ( 2014 ) investigated the spillover effect in the main five stock markets (US, UK, Germany, Japan, and France) and found a net spillover effect in the US stock market during the subprime mortgage crisis and Lehman Brothers bankruptcy from 2007 to 2008.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their study of long-run comovements in the stock market for the G7 countries between 1973 and early 2009, Menezes and Dionisio [43] find an overall long-run relationship governing the process of market integration and conclude that "the US market leads the G7 market space and the UK emerges as a regional attractor within the European context, which, in turn, is strongly affected by the North-American markets." Taking on a time-frequency perspective, our findings point to similar conclusions for the overlapping time interval.…”
Section: Discussionmentioning
confidence: 99%
“…The large stock prices increases or decreases, known as positive or negative shocks, are among the main symptoms of the turbulent periods. Such shocks could influence the investors, inducing them behaviors that are significantly different to those from quiet periods (Longin & Solnik, 2001;Lasfer et al, 2003;Rigobon, 2003;Menezes & Dionísio, 2011;Charles & Darné, 2014). In these circumstances, a shock from an important international market, such as the New York Stock Exchange (NYSE), which usually generates many breaking news in the international mass media, could significantly affects the returns and the volatility of other developed and emerging markets.…”
Section: Introductionmentioning
confidence: 99%